Knowing the Figure of KH. Munawar Al Badri Sang Paku Bumi, Da'wah Fighters from the North Coast - Jaya Mualimin; Abdul Aziz; Nursyamsiah; Abdul Ghofar; Abu Hasan Mubarok (PT FORMOSA CENDEKIA GLOBAL, 2022)
Every struggle of the ulama/kyai must have obstacles, obstacles and challenges, although relatively different but in principle the same, namely amar ma'rûf nahy munkar. KH. Munawar bin Kyai Badriyah bin Kyai Sarbian the originator and initiator of Islamic syi'ar broadcasters in the past Grinting era (1965s) known as Grinting is a black of culture, the village was left behind after being made aware of the importance of education, especially religious education in the 20s years later now different, advanced, high achievers and religious. It even became the village with the best educational participation rate. Through a qualitative approach with a narrative model and historical, descriptive, and literature methods. Success in spreading the mission of Islamic boarding school with its three teaching materials, namely reading the Qur'an, understanding tajwid and having good morals contributed to the millennial era, including in initiating Jam'iyah, and madrasa education.